The Epidemiological Characteristics of Stroke in Hunan Province, China - He, Wei; Liu, Yunhai; Feng, Jie; Huang, Qing; Xu, Ji; Liu, Xiaojuan; Yu, Cheng; Zhu, Wenbin; Wang, Te; Jin, Donghui; Liu, Huilin; Huang, Yuelong; et al. (Frontiers in Neurology, 2018)
Previous studies have shown that Hunan Province has a high incidence of stroke and a high proportion of intracerebral hemorrhage (ICH). Considering the changes over the past three decades, little is known about the current epidemiological characteristics of stroke in Hunan Province. In 2013, a cross-sectional study was conducted at 7 national disease surveillance points (DSPs) in Hunan Province. A multistage cluster sampling method was used to select a representative sample. A total of 21,156 participants aged 20 years and older were examined. Among the 21,156 participants, the number of prevalent strokes, incident strokes and deaths was 307, 87 and 36, respectively. The 2010 China census-standardized prevalence, incidence and mortality were 1,191.0 per 100,000 people [95% confidence interval (CI) 1,044.8-1,337.2], 333.6 per 100,000 person-years (95% CI 255.7-411.5) and 129.7 per 100,000 person-years (95% CI 81.1-178.3), respectively. Ischemic stroke (IS), ICH, subarachnoid hemorrhage (SAH), and stroke of undetermined type (UND) constituted 50.6%, 41.4%, 5.7% and 2.3% of all incident stroke cases, respectively. Tianxin, Liuyang, Wuling and Hongjiang have high proportions of ICH (61.5%, 58.3%, 60% and 50%, respectively). Hypertension is the most common risk factor for prevalent stroke (71.34%), followed by smoking (30.62%) and alcohol use (25.73%). In conclusion, Hunan Province has an extremely heavy stroke burden. The high proportion of ICH is not limited to the Changsha community; it represents an important issue for all of Hunan Province.